Development of model reading skill builders for Filipino students in high school - Ledesma, Lydia (Guevara) 1923- ([Quezon City s.n.], 1962)
This study gives a proposed solution to the two problems of our reading programs through formulation of forty reading comprehension materials on two levels of difficulty. These materials were geared to the background, interests, and needs of the Filipino students in high school.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Reading (Secondary education).